OSCC Exosomes Regulate miR-210-3p Targeting EFNA3 to Promote Oral Cancer Angiogenesis through the PI3K/AKT Pathway. (9th July 2020) - Wang, Hui; Wang, Lin; Zhou, Xiaocheng; Luo, Xinyue; Liu, Ke; Jiang, Erhui; Chen, Yang; Shao, Zhe; Shang, Zhengjun
Abstract : This study is aimed at determining how oral squamous cell carcinoma (OSCC) regulates the angiogenesis of HUVECs through miR-210-3p expression and exploring the relationship among miR-210-3p, its target protein, and the possible mechanism of angiogenesis regulation. miR-210-3p expression was detected in OSCC tissues and juxta cancerous tissues (JCT), and the relationship among miR-210-3p, microvessel density (MVD), and histopathologic features was analyzed. A conditioned medium (CM) of the OSCC cell line CAL27 was collected to stimulate human umbilical vein endothelial cells (HUVECs), and the miR-210-3p levels and tube formation capability of HUVECs were measured. The target protein level of miR-210-3p was altered; then, PI3K/AKT pathway activation in HUVECs was detected. miR-210-3p was tested in exosomes separated from CAL27 CM, and the transfer of miR-210-3p from OSCC exosomes to HUVECs was verified. Then, we found that the OSCC tissues had higher miR-210-3p levels than the JCT, and miR-210-3p level was positively correlated with MVD and tumor grade. CAL27 CM was able to elevate miR-210-3p levels in HUVECs and promoted tube formation. EFNA3 was the target gene of miR-210-3p, and ephrinA3 protein level was able to influence the migration and proliferation of HUVECs. The levels of phosphorylated AKT in the HUVECs increased when ephrinA3 was downregulated, and the upregulation of ephrinA3 resulted in the suppression of the PI3K/AKT pathway. miR-210-3p was detected in exosomes isolated from the CM of CAL27 cells, and miR-210-3p level in the HUVECs was elevated after absorbing the OSCC exosomes. In conclusion, miR-210-3p was more overexpressed in OSCC tissues than in the JCT. The exosomes secreted by OSCC cells were able to upregulate miR-210-3p expression and reduce ephrinA3 expression in HUVECs and promoted tube formation through the PI3K/AKT signaling pathway.